MANAGEMENT STRATEGY OF NINO CONI SANTANA NATIONAL PARK AT TUTUALA VILLAGE, TUTUALA SUB-DISTRICK, LAUTEM DISTRCK, TOMOR-LESTE - Edelmiro Jose De Deus; Wayan Windia; Ida Ayu Astarini (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Nino Coni Santana National Park had been suffered by illegal logging, and other activities that are not environmenknowleage. Lack of a security and knowledgeabout forest also contributeto increasethe damage of Nino Coni Santana National Park (1)The purpose of this research is to determine management strategy of Nino Coni National Park due to illegal logging in the area Tutuala and Mehara village at Tutuala sub-district,Lautem district, Timor Leste and determine management strategy of Nino Coni Santana National Park. Public perception obtained through questionnaires with purpose sampling method. The formula of management strategy for the damage in Nino Coni Santana National park use SWOT analysis to identify internal and external factors. The level of damage known by identifiy thearea due damaged by illegal logging.(2) The results showed that the damage by illegal logging at Nino Coni Santana national park caused because people are not involved in management of Nino Coni Santana National Park. The problems are illegal logging, encroachment,of forest, slash the wood harting wild animals, lack organization,andillegal grazing.(3) The management strategy of Nino Coni Santana National Park based on local culture, the establishment of a special UPTD that manage Coni Nino Santana forests, HKM and tourism programs, public development programs and cooperation of local people in order to utilize, surveillance and patrolling forests. In order to develop local knowledge as a base inNino Coni Santana National park,through HKM and tourism, Public socialization about the importance of forest. To measure the success of this management,should do monitoring, controlling andevaluation periodically by the government and involve the local people around Nino Cono Santana National Park.